ISLAMIC SYNCRETISM IN SAPTA DARMA IN SURABAYA - Ardi Tri Yuwono; Andi Sebastian; Shafiera binti Che Asmar (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
Every religious believer has a certain method to get closer to God. A deep desire to connect with God reflects spirituality that can change an individual's behaviour to be more positive. The interaction between Islam and Sapta Darma is a means to achieve inner peace that integrates physical and spiritual awareness. This research aims to describe the form of syncretism between Islam and Sapta Darma in Surabaya. The method used in this study is to combine field data and literature review with a qualitative approach. The syncretism between Islam and Sapta Darma in Surabaya is very pronounced, but this condition encourages individuals to maintain both teachings. This is due to their desire to achieve balance and well-being in spirituality. Islam and Sapta Darma are not only seen as an escape from life, but also as a new paradigm in understanding the concept of religiosity and spiritual values through syncretism. Syncretic religiosity has become part of the society of Surabaya and functions as a local cultural identity.